The state of functioning transport, freight forwarding and logistics companies and their responses to the pandemic crisis - Furtak, Klaudia (Zielona Góra: Faculty of Economics and Management Press)
The article attempts to present, on the basis of the existing survey research (questionnaires and interviews), subject literature, internet data as well as personal experiences and observations of the author (an employee of an international transport and logistics company), the general data regarding the influence of the COVID-19 pandemic on the functioning of transport, freight forwarding and logistics companies (referred to as TFL companies) and, additionally, the responses of these companies to the pandemic crisis.
Keywords: pandemic; COVID-19; TFL companies; pandemic crisis; transport; freight forwarding; logistics company; constructive impact; pandemia; branża TSL; kryzys pandemiczny; spedycja; logistyka